ECONOMIC DEVELOPMENT OF COLONIAL SURABAYA AND ITS IMPACT ON NATIVES, 1830-1930 - Nasution, - (Historia: Jurnal Pendidik dan Peneliti Sejarah, 2011)
This study explores the process of economic development of Surabaya residency in the period 1830-1930 and its implications for the natives’ economy. The indicator of economic development is focused on export of agricultural and export-import activities of Surabaya in 1830-1930. The natives’ economic progress will be seen at the level of their income. The minimum standard used to measure the level of prosperity is the per year income of a native.The rise and decline of the Surabaya economy during the period of Cultivation System and the liberal period can be observed from the export of agricultural products and the value of the foreign trade surplus. The highest value of foreign trade surplus in the Cultivation System period occurred in 1850s. At that time the overall value of foreign trade surplus of Surabaya showed was 0.54 per cent. The highest foreign trade surplus in liberal period was 0.96 per cent which occurred in 1920, when the price of sugar was rapidly increasing. The implication of the economic development of Surabaya for the native can also be differentiated between the period of the Cultivation System and the liberal period.  In the period of the Cultivation System the economic condition of people was really miserable, especially in sugar cane plantation areas. The hardship of the people in Surabaya was describe by the nineteenth-century historian Hageman as temporary slavery (tijdelijke slavernij). The economic condition of the people in Surabaya in liberal period can be considered prosperous, especially after the abolishment of the compulsory work. In the city of Surabaya which was the capital city of the residency, as a result of the expansion of trading, shipping and industry, employment was abundant and the people became prosperous too. After 1870 a skilled laborer (tukang) in the capital city of Surabaya received an income of 1.00- 1.50 guilders per day. The depression of the people resurfaced when the economic crisis hit 1930s. As a result, much investment went bankrupt. In addition, a number of development projects of the government had to be stopped which resulted in increasing unemployment.